The first find of the pond bat Myotis dasycneme (Boie, 1825) in Stavropol Territory and western Caucasus, Russia - A. A. Maslov; A. N. Ivanitzky; A. Yu. Alekseev (Юг России: экология, развитие)
The aim of the work was to describe the discovery of a pond bat Myotis dasycneme (Boie, 1825) in the vicinity of Zheleznovodsk, Stavropol Territory, Russia in August 2023.We examined the Letnei Merzloti Cave, an artificial tunnel about 400 metres long with small dead‐end caverns. The pond bat was found in a small dead‐end cavern. This is the first find of this species in the Stavropol region and the third find in the Caucasus.The first finds of the pond bat were made in the Western Caucasus in 1999 and 2003. This find provides more data about a small population of pond bats in the Caucasus. It is noteworthy that this species of bat (M. dasycneme), together with M. daubentonii, are the only known natural wild hosts of the Europian bat lissavirus virus type 2 in Europe. Given the fact that bats are considered natural hosts of all types of coronaviruses, and that the pond bat previously evidenced the circulation of both alpha and beta coronaviruses in the European population (Germany, the Netherlands), we must be aware of the potential of this species as a reservoir of pathogenic zoonotic coronaviruses.